2005
DOI: 10.1002/adsc.200505097
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide‐Catalyzed Additions of Acyl Phosphonates to Aldehydes: A New Acyl Donor for Benzoin‐Type Reactions

Abstract: Acyl phosphonates have been utilized as new acyl donors for cyanide-catalyzed benzoin-type reactions. Cyanation of acyl phosphonates, followed by a [1,2]-phosphoryl migration generates the active acyl anion intermediate. The presumed (cyano)phosphate anion reacts with a variety of aryl aldehydes to yield phosphate ester-protected, unsymmetrical benzoins in good to excellent yields. The unsymmetrical benzoin product can be obtained after deprotection of the phosphate ester with an aqueous amine solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Heterocyclic aldehydes provided the expected products 3e and 3g , albeit contaminated with isomeric benzoins 3f and 3h (Table , entries 5−8). This concurrent regioisomerization process was also pointed out by Johnson and co-workers . Whereas lowering the temperature (0 °C) provided the expected products without isomer contamination, increasing the catalyst load (30%) quickly furnished the isomeric products.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Heterocyclic aldehydes provided the expected products 3e and 3g , albeit contaminated with isomeric benzoins 3f and 3h (Table , entries 5−8). This concurrent regioisomerization process was also pointed out by Johnson and co-workers . Whereas lowering the temperature (0 °C) provided the expected products without isomer contamination, increasing the catalyst load (30%) quickly furnished the isomeric products.…”
supporting
confidence: 66%
“…We envisioned that the typical nucleophilic catalysis of benzoin and Stetter reactions might promote acylphosphonates to generate an appropriate concentration of the corresponding acyl anion equivalents that are sufficiently nucleophilic in order to participate in the reactions with electrophiles. It is very important to note that Johnson and co-workers very recently reported the viability of this approach in the synthesis of a variety of aromatic−aromatic cross-benzoin products 3 from aromatic acylphosphonates, with [18-crown-6/KCN] complex as catalyst in diethyl ether providing the optimal conditions (Scheme ) . Morover Kurihara reported stoichiometric strong base deprotonation of α-cyanophosphates generating cyano-phosphate anions 1b that react with a variety of electrophiles including aldehydes to provide 3 …”
mentioning
confidence: 99%
“…The proposed mechanism (Scheme 49) implies a cyanide-promoted [1,2]-Brook rearrangement 88 → 89 [337,338]. Acyl phosphonates also undergo cyanide-catalyzed additions to aldehydes [339]. A strategy utilizing N-heterocyclic carbenes (NHCs) derived from thiazolium salts has been developed for the generation of carbonyl anions from acylsilanes [340].…”
Section: An Intermediate Carbanionmentioning
confidence: 99%
“…Recently, we and others have shown that acyl phosphonates are potent acyl anion precursors and undergo nucleophile-promoted phosphonate−phosphate rearrangement to provide the corresponding acyl anion equivalents as reactive intermediates. Acyl phosphonates 1 , which are easily synthesized from acyl chloride and trialkyl phosphite in high yields, as the acyl anion precursors, and aldehydes as the electrophiles in the presence of a cyanide catalyst provide cross-benzoin products.…”
mentioning
confidence: 99%